Situational reflection as predictor of safe driving: Development and testing of the Driver Situational Reflection Scale (DSRS) - Ivars Austers; Kristīne Jaunzeme; Girts Dimdins; Inese Muzikante; Elīna Poļanska (Transportation Research Interdisciplinary Perspectives)
Understanding car drivers’ behavior should move beyond describing aspects of individual drivers’ behavior. This article proposes that cognitive representations of the interaction between drivers in terms of imagining other road users’ mental pictures of a certain road situation as well as the situation itself play an important role in reducing risky driving behavior. Consequently, the authors have developed a new method for measuring the degree to which drivers reflect on situations and take others’ perspectives in a traffic flow – the Driver Situational Reflection Scale (DSRS). The final version of the scale consists of two factors (dimensions): Caution, and Perspective-taking. These two factors showed good predictive validity in predicting positive and aberrant driving, as well as prosocial and aggressive driving (Studies 1A and 1B) and driving skills (Study 2).